A review of methods and indicators used to evaluate the ecological modifications generated by artificial structures on marine ecosystems. (15th May 2022) - Taormina, Bastien; Claquin, Pascal; Vivier, Baptiste; Navon, Maxine; Pezy, Jean-Philippe; Raoux, Aurore; Dauvin, Jean-Claude
Abstract: The current development of human activities at sea (e.g. land reclamation, maritime activity and marine renewable energy) is leading to a significant increase in the number of infrastructures installed in marine settings. These artificial structures provide new hard-bottom habitats for many marine organisms and can thus modify the structure and functioning of coastal ecosystems. In order to better evaluate the nature of these modifications as well as the potential benefits and/or impacts generated, it becomes essential to develop assessment methods that can be applied to a wide variety of study sites from harbours to coastal offshore environments. In this context, our study aims to review the different methods and indicators available which are used to measure the modifications of biodiversity and ecological functioning generated by such structures. Among the methods reviewed, we highlight some that were developed specifically for artificial structures, and others intended for various primary uses but which have been successfully transposed to artificial structures. Nevertheless, we also point out the lack of reliable methods concerning some biological ecosystem components impacted by artificial structures. In this context, we require the adaptation or creation of brand-new indicators to achieve a better characterisation of the ecological impacts generated by these structures. Overall, this study highlights a very high number of existing methods, which provide stakeholders with useful tools to study the impacts of artificial structures, and identifies the need to develop integrative indicators to enhance the deployment of new artificial structures. Highlights : This study comprehensively reviews methods for assessing the ecological modifications generated by artificial structures on marine settings. These methods are focusing on epibenthic and megafauna colonization, and on changes in ecosystem functioning. Indicators and methods focusing on megafauna colonization and ecosystem functioning already exist and were successfully applied to this topic. We highlighted a lack of reliable methods for the assessment of epibenthic colonization, useful recommendations to fill this gap were provided. We provide stakeholders with a catalogue of useful tools to characterize ecological impacts associated with AS, allowing to draw lessons for future deployments.